Simulation of Electron Acoustic Wave Propagation in Non-Uniform Magnetized Plasma - Hamid Reza Pakzad (Iranian Journal of Astronomy and Astrophysics)
The Propagation of electron acoustic solitary waves is studied in a plasmas consisting of hot and cold electrons and stationary ions and in the presence of nonuniform external magnetic field. Our simulation results in this paper show that the electron acoustic solitary waves radiate some amount of energy during their traveling through the varying magnetic field. The important point is that we do not have other dissipative sources like particle interaction or viscosity effects, in this model. We also find that the electron density waves moves with a small wavelets around the central electron density even if the external magnetic field is constant.We propose to perform a laboratory experiment which will be able to identify the special new features of the electron acoustic waves propagation in a magnetized plasma with external varying magnetic field in which have been predicted in this investigation. Furthermore, our theoretical analysis brings a possibility to develop more refined theories of nonlinear acoustic waves that may occur in astrophysical nonuniform magnetixed plasmas.